Use Cases for Abnormal Behaviour Detection in Smart Homes - Lyons, Paul; Tran, An C.; Marsland, Stephen; Dietrich, Jens; Guesgen, Hans W. (Springer, 2010)
While people have many ideas about how a smart home should react to particular behaviours from their inhabitant, there seems to have been relatively little attempt to organise this systematically. In this paper, we attempt to rectify this in consideration of context awareness and novelty detection for a smart home that monitors its inhabitant for illness and unexpected behaviour. We do this through the concept of the Use Case, which is used in software engineering to specify the behaviour of a system. We describe a set of scenarios and the possible outputs that the smart home could give and introduce the SHMUC Repository of Smart Home Use Cases. Based on this, we can consider how probabilistic and logic-based reasoning systems would produce different capabilities.
Keywords: Abnormal behaviour detection; Context awareness; Smart home; Fields of Research::290000 Engineering and Technology::291100 Environmental Engineering::291101 Environmental engineering modelling